Co-combustion of methane hydrate and conventional fuels. (15th July 2023) - Gaidukova, O.S.; Dorokhov, V.V.; Misyura, S.Ya.; Morozov, V.S.; Shlegel, N.E.; Strizhak, P.A.
Graphical abstract: Highlights: Gasoline initiates methane hydrate combustion at low temperatures. Gas hydrate intensifies the combustion of low-rank solid fuels. Anthropogenic emissions from the combustion are low when gas hydrates are used. Co-combustion of fuels and hydrates has high environmental and energy benefits. Solutions are proposed to intensify the combustion of fuel blends. Abstract: This paper presents the experimental data on the co-combustion of methane hydrate powder with conventional fuels: gasoline, kerosene, Diesel fuel, coal, and coal slime. For the experiments we used a laboratory-scale combustion chamber based on an induction system on the walls and a spark ignition system. Fuel ignition delay times were measured during separate and simultaneous supply of fuel components. It was found that the combustion of slow-burning fuels can be intensified by injecting methane hydrate granules. Liquid fuels with high concentrations of light fractions can be used to intensify the combustion of methane hydrate at relatively low temperatures in the combustion chamber. After recording the concentrations of the main components of combustion products, we rationalized the environmental benefits of gas hydrates used as the primary and secondary fuel components. The relative efficiency coefficients were calculated for fuels in terms of their environmental, economic, and energy performance indicators. We also formulated recommendations on the co-combustion of gas hydrates with conventional fuels in combustion chambers. Finally, we proposed engineering solutions for the effective use of gas hydrates in power plants.